The Effect of Online Group Education on Promoting Knowledge, Motivation, Self-Efficacy, Self-Care Behaviors and Preventing Uncontrolled Blood Pressure in Hypertensive Patients: A Quasi-Experiment Study - Upoyo, Arif Setyo; Sari, Yunita; Taufik, Agis; Anam, Akhyarul; Kuswati, Ani (SAGE open nursing, 2024)
Introduction Hypertensive patients may lack time to visit clinics and attend educational sessions, resulting in poor blood pressure control. Uncontrolled blood pressure in people with hypertension can increase the risk of heart disease and stroke. Objective The specific purpose of this study was to determine the effect of online group education on knowledge, motivation, self-efficacy, self-care behavior, and blood pressure control of hypertensive patients. Method The research method used a quasi-experiment method. The subjects were hypertensive patients in Indonesia. The sampling technique used was cluster random sampling. Total sampling consisted of 96 participants, consisting of 48 intervention groups and 48 control groups. The inclusion criteria in the study were patients with primary hypertension who were willing to become research respondents. The exclusion criteria in this study were respondents who were sick and unable to follow therapy, had hearing problems, and had complications of other diseases (kidney disease, heart disease, diabetes mellitus, and stroke). Data collection methods include observation. The instruments used were the HKLS, HBP-SCP questionnaire, and Sphygmomanometer digital. Result Data analysis using repeated ANOVA and Friedman tests. There was a significant decrease in systolic (p < .001) and diastolic (p = .001) blood pressure and an increase in knowledge (p < .001), motivation (p < .001), self-efficacy (p < .001), and self-care behavior (p < .001) in the intervention group. Conclusion Online group education effectively reduces blood pressure and increases self-care behaviors in hypertensive patients.